2010
DOI: 10.1007/s10593-010-0589-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of photochromic bisfulgimides by the condensation of (3Z)-3-[1-(2,5-dimethyl-3-thienyl)-ethylidene]-4-isopropylidene-2,5-furandione with aromatic diamines

Abstract: The first representatives of thiophene derivatives with two fulgimide fragments in one molecule have been obtained by the condensation of (3Z)-3- [1-(2,5-dimethyl-3-thienyl)ethylidene]-4-isopropylidene-2,5-furandione with aromatic diamines. The photochromic properties of the obtained compounds have been investigated and the effect of a spacer, linking the two fulgimide fragments, on the reaction rates of photocoloration and photodecoloration of these compounds has been studied.Fulgimides of the thiophene serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Fulgimide derivatives have been only scarcely used in dimers. To the best of our knowledge, only one series has been reported by Luyksaar et al, 142 who have synthesized bisfulgimides, connected through various types of aromatic bridges (42). In the case of the FG open form, a Z/E isomerisation also occurs (and thus provides a third photoactive state).…”
Section: Dyads Of Fulgimides Spiropyrans and Dihydropyrenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fulgimide derivatives have been only scarcely used in dimers. To the best of our knowledge, only one series has been reported by Luyksaar et al, 142 who have synthesized bisfulgimides, connected through various types of aromatic bridges (42). In the case of the FG open form, a Z/E isomerisation also occurs (and thus provides a third photoactive state).…”
Section: Dyads Of Fulgimides Spiropyrans and Dihydropyrenesmentioning
confidence: 99%
“…Chindam et al have rationalised the optical properties of the di-fulgimide series reported by Luyksaar et al (compound 42), 142 and they investigated the effect of chemical substitution on the optical properties of new dissymmetric compounds, designed to access multi-addressable systems. 262 From the calculations on the experimentally available compounds, the mixed co form was predicted to exist though it was not detected experimentally, an apparent discrepancy that might be ascribed to the symmetric nature of the compounds, yielding hardly distinguishable optical signatures for the co and cc isomers.…”
Section: Dimers and Multimers Of Other Photochromesmentioning
confidence: 99%
“…To our knowledge, multifunctional molecular switches are one of the most prospective photoswitches, fulgide/fulgimide, and diarylethene have attracted considerable attention as the most promising candidates. Currently, many photochromic switches which consist of two or more monomers have been reported . Two photochromic units can be combined into a new multifunctional photochromic molecule by a bridged linker, one can be converted to another by proper wavelength irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many photochromic switches which consist of two or more monomers have been reported. [18][19][20][21] Two photochromic units can be combined into a new multifunctional photochromic molecule by a bridged linker, one can be converted to another by proper wavelength irradiation. These multifunctional molecules need to display different optical signals when they proceed a mutual transformation for their different states.…”
mentioning
confidence: 99%